Molecular phylogeny reveals a new genus of freshwater mussels from the Mekong River Basin (Bivalvia: Unionidae) - Jeratthitikul, Ekgachai; Sutcharit, Chirasak; Ngor, Peng Bun; Prasankok, Pongpun (European Journal of Taxonomy, 2021)
A new genus of freshwater mussels (Bivalvia: Unionidae) is described from the Mekong River Basin as Namkongnaia gen. nov. The validity of the new genus is supported by its unique conchological characteristics, namely the lack of hinge dentition and elongated shells, together with its evolutionary distinctiveness as estimated by multi-locus phylogenetic analyses (mitochondrial COI and 16S, and nuclear 28S genes). The new genus includes two lineages with deep divergence, shown by 5.10% uncorrected COI p-distance. One lineage is a type species described herein as Namkongnaia inkhavilayi gen. et sp. nov. The other is a recognized species under the name ‘Pilsbryoconcha lemeslei (Morelet, 1875)’. Molecular phylogenetic analysis further shows that the new genus belongs to the tribe Pseudodontini, and evolutionarily is closely related to the genus Monodontina Conrad, 1853. However, its conchology is similar to the genus Pilsbryoconcha Simpson, 1900. Time-calibrated phylogeny suggests that the main radiation events of the tribe Pseudodontini occurred during the Late Cretaceous to the Eocene, with the divergence between the new genus and Monodontina placed in the Miocene. The discovery of new freshwater mussel taxa in this study highlights the importance of the Mekong River Basin as one of the world’s biodiversity hotspots for freshwater fauna.